Effect Of Compost Tea and JADAM Microorganism Solution On Growth Of Chili Pepper In PT. Cinquer Agro Nusantara - Khairani, Iffa Afiqa; Novriadi, Novriadi; Wandasari, Septi Putri; Nanda, M. Zulhiyadi; Anshori, Andi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2023)
Chili pepper (Capsicum frustescens) is herbaceous plant from the family Solanaceae which is massively cultivated in Indonesia. It also can be used as raw material for food product and pharmacy industries. Organic fertilizer usage has been both a solution to increase productivity and a replacement to chemical fertilizer usage. The aim of this study is to examine the effect of compost tea organic fertilizer and JADAM Microorganism Solution (JMS) on the growth of chili pepper in PT. Cinquer Agro Nusantara, Bangka Belitung. This research used a completely randomized design with 15 unit treatments which were divided into control group, compost tea group, and JMS group. The result showed that the plant group with JMS performed the highest height expansion, increasing the number of leaves significantly compared to control and compost tea group. This study concludes that application of compost tea and JADAM Microorganism Solution (JMS) as organic fertilizer on C. frustescens can increase the plant’s growth.Keywords : chili pepper, compost tea, JADAM microorganism solution